Tacitean Visual Narrative - Waddell, Philip (Bloomsbury Publishing Plc, 2020)
Cover page -- Halftitle page -- Series page -- Title page -- Copyright page -- Dedication -- Contents -- Figures -- Acknowledgments -- Introduction1 -- Classics and Film -- Roman Visuality -- The Romans' Visual World -- Feldherr's Visual Historiography -- Visual Historiography -- Narratology -- Toward an Understanding of Visual Narrative -- Visual Methodology -- Film Paradigm: The Classical Hollywood Film -- How Classical Hollywood Cinema Applies to Tacitus -- Part One Lens and Voice -- 1 Focalizing Empire -- Focalization and Visual Control -- The Third Man -- Pompeian Ariadne -- Tiberius -- Asinius Gallus -- Agrippina at the Bridge -- Choosing a Successor -- Sejanus -- Plotting against Drusus -- Destroying the House of Germanicus -- Convincing Tiberius -- Agrippina the Younger -- The Murder of Agrippina: Th e Ideal Spectator and the Shot-Reverse-Shot -- Strangers on a Train -- Nero's Plan -- What the Rowers Saw -- Desertion, Murder, and Aft ermath -- Final Thoughts -- 2 Vox Caesaris, Vox Taciti: Imperial Alignment -- Excursus, Voice, and Alignment -- Alignment -- Pompeian Narcissus -- Murder, My Sweet -- Tiberius: The (Mis)Rule of Law -- Tiberius and Justice -- Lex Maiestatis -- Rule of Law -- State of the Empire -- Tiberian Rome -- Claudius: The Professor- in-Chief -- The Oblivious Scholar -- Altering the Alphabet -- Expanding the Pomerium -- Final Thoughts -- 3 The Directed Gaze and the Construction of Meaning -- Imperial Close-ups and Touch of Evil -- Tiberius -- The Trial of Calpurnius Piso -- The Persecution of Nero Caesar -- Nero -- The Maltese Falcon and the Threatening Gaze -- The Nobiles -- Nero -- Agrippina -- Octavia -- Damnatio Memoriae, Rebecca, and Watching the Invisible -- Invisible Cursus -- Inverted Thanksgivings -- Invisible Ancestors -- Final Thoughts -- Part Two Transition and Connection.